Desempleo y protección social : el caso colombiano (2019)
ABSTRACT: The objective of this essay is to recognize the unemployment phenomenon as a problem that affects social welfare and requires, therefore, responses from the State and society in terms of social protection. Likewise, social protection mechanisms against unemployment in Colombia are also discussed.